1984
DOI: 10.1099/00221287-130-12-3219
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic Effects of Mutations at the A and B Incompatibility Factors in Coprinus cinereus

Abstract: Mutated A and B incompatibility factors of Coprinus cinereus (Amut and Bmut) were recovered from fruit bodies produced on common-A and common-B heterokaryons, respectively, following mutagenesis. The Amut hyphal cells were either uninucleate or binucleate and had pseudoclamps irregularly scattered along the hyphae. The Bmut hyphal cells were predominantly uninucleate and had no clamp structures. Amut Bmut double mutants constructed from these Amut and Bmut strains were predominantly binucleate, had true clamps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 16 publications
3
83
0
Order By: Relevance
“…Rare mutations in these loci lead to the formation of selfcompatible Amut Bmut homokaryons that mimic a dikaryon. In particular, such homokaryons can have the ability to form fruiting bodies (Swamy et al, 1984), demonstrating the regulatory function of the matingtype loci in fruiting body development. In the initial stage of fruiting body (basidiocarp) development, hyphae form localized, highly branched structures termed hyphal knots (Matthews & Niederpruem, 1972 ; reviewed by Ku$ es, 2000) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Rare mutations in these loci lead to the formation of selfcompatible Amut Bmut homokaryons that mimic a dikaryon. In particular, such homokaryons can have the ability to form fruiting bodies (Swamy et al, 1984), demonstrating the regulatory function of the matingtype loci in fruiting body development. In the initial stage of fruiting body (basidiocarp) development, hyphae form localized, highly branched structures termed hyphal knots (Matthews & Niederpruem, 1972 ; reviewed by Ku$ es, 2000) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As a receptor strain for these silencing plasmids we used the self-compatible homokaryon AmutBmut. This particular strain carries specific mutations in both mating-type loci (A43mut and B43mut) that enable the formation of fruiting bodies without prior mating to another strain (Swamy 1984;Boulianne et al 2000). It shows typical characteristics of the dikaryon such as the formation of fused clamp cells at hyphal septa and it has been used to screen for mutations affecting dikaryotic phenotypes, such as clamp connection formation (Inada et al 2001), fruiting body development (Chiu and Moore 1990;Granado et al 1997;Muraguchi et al 2008), and meiosis (Cummings et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Strains and growth conditions C. cinerea strains are derived from the AmutBmut genetic background (A43mut B43mut pab1-1) (Swamy 1984). Strains were grown on YMG/T (0.4% yeast extract, 1% malt extract, 0.4% glucose, 100 mg/liter tryptophan, and 1% agar) and MM (0.1% KH 2 PO 4 , 0.225% Na 2 HPO 4 , 0.029% Na 2 SO 4 , 0.05% diammonium tartrate, 0.025% MgSO 4 · 7H 2 O, 4 · 10 25 % thiamine, 0.005% adenine sulfate, 0.2% asparagine, 1% glucose, and 1% agar) media at 37° (Rao and Niederpruem 1969;Granado et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…In classical crosses of distantly related C. cinerea strains, large proportions of progenies will perform poorly in growth and/or in fruiting body development . Since positively selected for their ability to form fruiting bodies without a prior need of mating, self-compatible haploid homokaryons present strains with an expected good-quality pool of fruiting genes (Swamy et al 1984). By repeated backcrosses against strong, fruiting-proficient, self-compatible homokaryons, monokaryons co-isogenic to these homokaryons have been obtained carrying such good-quality pool of fruiting genes .…”
Section: Genetic Access Of Fruiting Body Developmentmentioning
confidence: 99%
“…clamps cells and clamp cell fusion; Kües et al 1992, 1994a,c, Badalyan et al 2004), the A mating type genes were shown to induce hyphal knot and primordia development ) and the B mating type genes to support the A mating type genes in initiation of fruiting body development and to act in fruiting body maturation at the stage of karyogamy (Kües et al 2002b). Therefore not surprisingly, certain mutations in the mating type loci (Kües et al 1994b, Pardo et al 1996, Olesnicky et al 1999, Srivilai et al 2006b) make fruiting body development independent from dikaryon formation (Swamy et al 1984). Basidiospores with such mutations germinate into a self-compatible, fertile mycelium with a dikaryon-like appearance: it has clamp cells at the hyphal septa and often two haploid nuclei in the hyphal cells -since these nuclei are genetic identical, the self-compatible mycelium is called a homokaryon: Also like the dikaryon, under appropriate environmental conditions fruiting bodies develop on the homokaryotic mycelium (Fig.…”
Section: Genetic Access Of Fruiting Body Developmentmentioning
confidence: 99%